Essays in Applied Microeconomics - Examining Land Restitution In a Post-Conflict Context - Crowther, Naomi (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2025)
This thesis explores the multi-faceted effects of land restitution in the wake of armed conflict, in the context of Colombia. It offers the first set of empirical studies of how formerly displaced peoples' lives are altered by restitution, alongside insights into the reception within their receiving communities. Drawing upon administrative, census, and geospatial data, I construct a novel dataset which enables causal analysis of short and mid-term effects. I explore the effects on agricultural investment decisions, household resource allocations towards human capital accumulation and labour supply, and the extent of social integration. Findings suggest land restitution may be a valuable tool to successfully reintegrate internally displaced people into communities and interrupt the deleterious cycle triggered by displacement. The research also uncovered shortfalls in the implementation of the policy which should be addressed in the future to ensure benefits reach the most disempowered.
APPROVED
Keywords: Applied Microeconomics; Inequality; Gender; Post-Conflict